Blogging - Rettberg, Jill Walker (Cambridge : Polity, 2014)
Provides an accessible study of blogging and places it in a historical, theoretical and contemporary context. Jill Walker Rettberg discusses the ways blogs are integrated into the mainstream social media ecology, where comments and links from Twitter and Facebook may be more important than the network between blogs that was significant five years ago, and questions the shift towards increased commercialization and corporate control of blogs. The book also analyses how smartphones with cameras and social media have led a shift towards more visual emphasis in blogs. The book is packed with examples that show how blogging and related genres are changing media and communication.--
1. What is a blog? -- 2. From bards to blogs -- 3. Blogs, communities and networks -- 4. Citizen journalists? -- 5. Blogs as narratives -- 6. Blogging brands -- 7. The future of blogging.
'Revised and updated'--Cover.
Previous edition : 2008.
Includes bibliographical references and index.
Keywords: Blogs; Blogs -- Social aspects; Blogs -- Political aspects